2014
DOI: 10.1002/jctb.4471
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced bioremediation of oily sludge using co‐culture of specific bacterial and yeast strains

Abstract: BACKGROUND Considerable volumes of petrochemical oily sludge can be generated from oil production and processing activities. Total petroleum hydrocarbons (TPH) contained in oily sludge are detrimental to human health and the environment. Thus, oily sludge is classified as a priority environmental pollutant by the US Environmental Protection Agency and it must be treated properly before discharge into the environment. RESULTS In this study, a functional microbial consortium consisting of Bacillus subtilis, Baci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(9 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…Kamyabi et al [13] also reported that an additional 20% of pyrene removal was achieved by combined cultures in comparison to individual cultures. Other studies have also described the higher ability of consortium to degrade petroleum pollutants [18,39]. The negligible TPH removal (3.8%) observed in the control reactor (A5) indicated that the bacterial populations were responsible for hydrocarbon degradation in the reactors A1-A4.…”
Section: Relation Between Crude Oil Degradation and Cell Growthmentioning
confidence: 89%
See 2 more Smart Citations
“…Kamyabi et al [13] also reported that an additional 20% of pyrene removal was achieved by combined cultures in comparison to individual cultures. Other studies have also described the higher ability of consortium to degrade petroleum pollutants [18,39]. The negligible TPH removal (3.8%) observed in the control reactor (A5) indicated that the bacterial populations were responsible for hydrocarbon degradation in the reactors A1-A4.…”
Section: Relation Between Crude Oil Degradation and Cell Growthmentioning
confidence: 89%
“…Hence, these two strains presented the synergistic effect for TPH biodegradation when they are used in the mixed culture. Several authors [18,35,36] already reported that pure single strains were not able to degrade crude oil effectively compared to their consortium. The positive effects of bacterial consortium compared to individual strains will be deeply discussed in section 3.3.1.…”
Section: 23 Synergistic Effect Of the Strainsmentioning
confidence: 99%
See 1 more Smart Citation
“…Bacterial-fungal co-cultures can also enhance bioremediation of petroleum hydrocarbons (Zanaroli et al 2010;Li & Li 2011;He et al 2014;Qiao et al 2014;Ma et al 2015). Li & Li (2011) revealed that co-inoculation of hydrocarbon polluted mangrove sediment with Cunninghamella echinulate and Vibrio rumoiensis led to a more efficient petroleum hydrocarbons bioremediation than the sum of the individual degradations obtained in axenic cultures of the fungus or bacterium.…”
Section: Bio-augmentation With Mixed Bacterial-fungal Consortiamentioning
confidence: 99%
“…In oil fields, hydrocarbon contamination is an inevitable problem during the upstream operations of the petroleum industry, which can poses significant ecological risks . Every year, billions of barrels of produced water and thousands of tons of oil‐contaminated soil are generated in the oil fields.…”
Section: Introductionmentioning
confidence: 99%